1992
DOI: 10.3109/08037059209065122
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Retinal Vascular Changes: Relationship to Left Ventricular Hypertrophy and Arteriolar Changes Before and After Treatment

Abstract: Eye-ground-photos were taken in twenty-eight previously untreated men with mild to moderate essential hypertension. The same eye was evaluated before and after 26 weeks of double-blind treatment with Enalapril or Hydrochlorothiazide. The vascular changes were assessed by using a more elaborate and refined grading than the Keith-Wagener-Barker scale. All photos were examined by the same observer without knowledge of blood pressure, type of treatment or the order in which the photos had been taken. There were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
2
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 22 publications
0
35
2
1
Order By: Relevance
“…The first important finding is that the incidences of proteinuria and advanced retinal Although it is well established that echocardiographicallydetermined LVH is the most important prognostic index of target organ damage in hypertensive patients, renal and retinal damage also has been shown to be important and to have prognostic significance (1)(2)(3)(13)(14)(15) The Framingham heart study demonstrated that in the ambulatory general population, proteinuria carries a substantial risk, with the mortality rate increased by three fold (15). Proteinuria was three times as commonin hypertensive persons, and was two times as commonin persons with electrocardiographicallydetermined LVH ( 1 5).…”
Section: Discussionmentioning
confidence: 99%
“…The first important finding is that the incidences of proteinuria and advanced retinal Although it is well established that echocardiographicallydetermined LVH is the most important prognostic index of target organ damage in hypertensive patients, renal and retinal damage also has been shown to be important and to have prognostic significance (1)(2)(3)(13)(14)(15) The Framingham heart study demonstrated that in the ambulatory general population, proteinuria carries a substantial risk, with the mortality rate increased by three fold (15). Proteinuria was three times as commonin hypertensive persons, and was two times as commonin persons with electrocardiographicallydetermined LVH ( 1 5).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is interesting that diuretics prevent hypertension in experimental hyperuricemia but, unlike angiotensin-converting enzyme inhibitors, do not block the development of the renal arteriolopathy (60). Similarly, a study in humans found that angiotensin-converting enzyme inhibitors are able to cause regression of retinal microvascular disease in hypertensive patients but diuretic therapy was without benefit (165). Again, these studies in composite suggest that diuretics, likely by raising uric acid levels and stimulating the renin angiotensin system, may accelerate the development of renal microvascular disease and thereby predispose the patient to renal progression.…”
Section: Specific Characteristics That Favor An Increased Risk For Rementioning
confidence: 98%
“…Studies have demonstrated regression of hypertensive retinopathy signs in response to BP reduction and that regression is different in response to different antihypertensive regimens (eg, angiotensin-converting enzyme inhibitors seem to have a more favorable effect on the retinal vasculature). [109][110][111] Changes in retinal vasculature, markers of hypertensive state, may act as therapeutic targets capable of reflecting the effectiveness of antihypertensive drug treatment in controlling elevated BP values. Nevertheless, data describing the impact of antihypertensive therapy on retinal vascular changes are still lacking.…”
Section: Can Retinal Vascular Imaging Be a Surrogate Measure To Evalumentioning
confidence: 99%